Novel Sirolimus–Coated Balloon Catheter: In Vivo Evaluation in a Porcine Coronary Model. (April 2016) - Clever, Yvonne Patricia; Peters, Daniel; Calisse, Jorge; Bettink, Stephanie; Berg, Madeleine-Caroline; Sperling, Christian; Stoever, Michael; Cremers, Bodo; Kelsch, Bettina; Böhm, Michael; Speck, Ulrich; Scheller, Bruno
Abstract : Background—: Limus-eluting stents are dominating coronary interventions, although paclitaxel is the only drug on balloon catheters with proven inhibition of restenosis. Neointimal inhibition by limus-coated balloons has been shown in few animal studies, but data from randomized clinical trials are not available. The aim of the present preclinical studies was to achieve high and persistent sirolimus levels in the vessel wall after administration by a coated balloon. Methods and Results—: Different coating formulations and doses were studied in the porcine coronary model to investigate sirolimus tissue levels at different time points as well as efficacy at 1 month using quantitative coronary angiography and histomorphometry. Loss of the selected coating in the valve, guiding catheter, and blood was low (2±14% of dose). Acute drug transfer to the vessel wall was 14.4±4.6% with the crystalline coating, whereas the amorphous coatings were less effective in this respect. Persistence of sirolimus in the vessel wall until 1 month was 40% to 50% of the transferred drug. At 1-month follow-up, a modest but significant reduction of neointimal growth was demonstrated in a dose range from 4 μg/mm 2 to 2×7 μg/mm 2, for example, maximum neointimal thickness of 0.38±0.13 versus 0.65±0.21 mm in the uncoated control group. Conclusions—: Various sirolimus-coated balloons effectively reduce neointimal proliferation in the porcine coronary model but differ considerably in retention time in the vessel wall. It has to be determined if such a formulation with persistent high vessel concentration will result in a relevant clinical effect.